Strategi Ketahanan Pangan dari Basis Lokal: Integrasi Prinsip Permakultur dalam Teknologi Pangan yang Berkelanjutan - Rika Nuryani Suwarno (Indonesian, 2024)
This article discusses strategies for food security from local bases through the integration of permaculture principles into sustainable food technology. This approach is considered a promising solution to address global challenges related to food security. Permaculture principles, such as diversity, closed-loop systems, and engagement with nature, are integrated into the design of agricultural and food systems. Sustainable food technologies, such as vertical farming, environmentally friendly food processing, and the use of renewable energy, are integral parts of this strategy. Through case studies and analysis, this article illustrates the success of this integration in increasing agricultural productivity, strengthening local food security, and reducing negative environmental impacts. Challenges and next steps are also discussed to overcome barriers to implementing this strategy. The integration of permaculture principles into sustainable food technology offers a holistic approach to building sustainable and resilient food security from local bases.